An Evaluation of The Use of Tiktok Shop as A Marketing Information System for Hijab SMEs in Bandung - Ines Khoiriyah; Faiza Renaldi; Dea Destiani (Publikasi Indonesia, 2026)
This study aimed to evaluate the use of TikTok Shop as a marketing information system for hijab MSMEs in Bandung City using the Information Systems Success Model developed by DeLone and McLean. The study employed a quantitative approach using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method. Data were collected through questionnaires distributed to 100 hijab MSME actors selected using a purposive sampling technique. The results showed that all constructs met the validity and reliability criteria. In addition, System Quality and Information Quality had positive and significant effects on User Satisfaction, while User Satisfaction had a positive and significant effect on Marketing Performance. These findings indicate that TikTok Shop can function as a marketing information system that supports increased user satisfaction and marketing performance among hijab MSMEs. The development of TikTok Shop has encouraged its utilization not only as a social commerce platform but also as a marketing information system. However, evaluations of this utilization remain limited. Therefore, this study evaluated the use of TikTok Shop as a marketing information system for hijab MSMEs in Bandung City using the Information Systems Success Model. The study employed a quantitative approach with the SEM-PLS method involving 100 hijab MSME actors selected through purposive sampling. The results demonstrated that all constructs fulfilled the validity and reliability criteria. System Quality and Information Quality had positive and significant effects on User Satisfaction, with Information Quality exerting a stronger influence than System Quality.